Magneto-Dielectric Synergy and Multiscale Hierarchical Structure Design Enable Flexible Multipurpose Microwave Absorption and Infrared Stealth Compatibility - Chen Li; Leilei Liang; Baoshan Zhang; Yi Yang; Guangbin Ji (Nano-Micro Letters)
Highlights A multiscale hierarchical structure design, integrating wrinkled MXene radar-infrared shielding layer and flexible Fe3O4@C/PDMS microwave absorption layer The assembled stealth devices realize a near-perfect stealth capability in both X-band (8-12 GHz) and long-wave infrared (8-14 µm) wavelength ranges. The optimal device demonstrates exceptional curved surface conformability, self-cleaning capability (contact angle ≈ 129°), and abrasion resistance (recovery time ≈ 5 s).